Inhibition of dipeptidyl peptidase IV by fexofenadine: Virtual screening study - Ihab M. Almasri, Mohammad K. Mohammad, Mutasem O. Taha (Journal of Applied Pharmaceutical Science, 2019)
Dipeptidyl peptidase IV (DPP IV) is relatively new anti-diabetic target. DPP IV inhibitors lower fasting and postprandial glucose concentrations by preventing the degradation of the natural hypoglycemic incretin hormones: glucose-dependent insulinotropic peptide and glucagon-like peptide-1. In this work, the high throughput docking software FRED was used as a virtual screening tool against in house built drug database to discover new DPP IV inhibitors. One of the highest ranking hits, the antihistamine drug fexofenadine, was found to inhibit recombinant human DPP IV in vitro with IC50 = 4.6 (±1.0) μM. The anti-diabetic effect of fexofenadine was validated in vivo by oral glucose tolerance test. These results could be helpful in the development of novel DPP IV inhibitors based on fexofenadine scaffold for the treatment of type 2 diabetes.
Keywords: Fexofenadine, DPP IV inhibition, virtual screening, docking, OGTT.